2003
DOI: 10.1124/jpet.103.052068
|View full text |Cite
|
Sign up to set email alerts
|

Role of Peripheral Benzodiazepine Receptors in Mitochondrial, Cellular, and Cardiac Damage Induced by Oxidative Stress and Ischemia-Reperfusion

Abstract: Mitochondrial dysfunction has been identified as a possible early event in ischemia-reperfusion damage. The peripheral benzodiazepine receptor, a mitochondrial inner membrane protein, has already been proposed to play a role in mitochondrial regulation, although its exact function remains unclear. The aim of this work was to determine the role of peripheral benzodiazepine receptor in ischemia-reperfusion injury and to test the potential beneficial effect of a novel potent peripheral benzodiazepine receptor lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
50
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 40 publications
3
50
0
1
Order By: Relevance
“…Several reports suggest that PBR ligands might modulate apoptotic responses (Bono et al, 1999) and play an antiapoptotic role in oxidative stress conditions such as ischemia-reperfusion (Carayon et al, 1996). In agreement with this role, Leducq et al (2003) showed that the irreversible PBR ligand SSR180575 prevented the cellular damages against oxidative stress and cardiac injuries induced by ischemia-reperfusion in rodents, but the mechanism involved in these effects remains unclear.…”
mentioning
confidence: 79%
“…Several reports suggest that PBR ligands might modulate apoptotic responses (Bono et al, 1999) and play an antiapoptotic role in oxidative stress conditions such as ischemia-reperfusion (Carayon et al, 1996). In agreement with this role, Leducq et al (2003) showed that the irreversible PBR ligand SSR180575 prevented the cellular damages against oxidative stress and cardiac injuries induced by ischemia-reperfusion in rodents, but the mechanism involved in these effects remains unclear.…”
mentioning
confidence: 79%
“…Additional proteins such as the translocator protein 18 kDa (TSPO), formerly known as the peripheral benzodiazepine receptor, have been shown to interact with proteins implicated in mPTP formation and potentially regulate the pore (Veenman et al, 2007). Selective TSPO ligands, such as chlorodiazepam (Ro5-4864) (Obame et al, 2007) or 7-chloro-N,N,5-trimethyl-4-oxo-3-phenyl-3,5-dihydro-4H-pyridazino[4,5-b]indole-1-acetamide (SSR180575) (Leducq et al, 2003), were reported to provide cardioprotection in preclinical models of I/R. The pro-and antiapoptotic Bcl-2 family proteins regulate mitochondrial permeability transition either by directly and independently forming a membrane channel or by interaction with mitochondrial membrane proteins such as VDAC (Shimizu et al, 1999) or adenine nucleotide translocase (Marzo et al, 1998).…”
mentioning
confidence: 99%
“…This showed the relative reduction of CMI% in the presence of diazepam. Consistently, several studies have shown that the presence of PBR ligands, including Ro5-4864 and SSR180575, could reduce oxidative stress, thereby preventing cardiac hypertrophy (3,23,24). Oxidative stress is implicated in development and progression of cardiac hypertrophy (25).…”
Section: Discussionmentioning
confidence: 71%
“…Similarly, our results showed for the first time that diazepam, as a common clinical drug, could prevent isoproterenol-induced cardiac hypertrophy, which could probably be explained by the above-mentioned modulatory effect of this drug as a PBR ligand. On the other hand, several studies have shown that diazepam was able to affect cells by mechanisms related or unrelated to PBRs (24,26). For example, diazepam decreased the Ca 2+ transient and the L-type Ca 2+ channel, which are both important in the negative inotropism and chronotropism caused by this drug (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%